TRANSFER PRICING AND COMPANY CHARACTERISTICS IN EXPLAINING TAX AVOIDANCE: EMPIRICAL EVIDENCE IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SUB-SECTOR - Rosmadina, Rosmadina; Pakkawaru, Muhammad Ilham; Pratiwi, Ni Made Suwitri; Mile, Yuldi; Rhamadhani, Rika Febby (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2026)
This study examines how 2tax avoidance among food and beverage manufacturing businesses listed on the Indonesia Stock Exchange between 2020 - 2024 is impacted by transfer pricing and company characteristics, particularly company size, leverage, and profitability. The study uses secondary data from annual financial reports obtained from the Indonesia Stock Exchange and employs a quantitative panel data regression methodology. Purposive sampling was used to choose the sample, and 60 observations were obtained. EViews 12 software was used to analyze the data. The results show that while transfer pricing and leverage have no discernible impact on tax avoidance, company size and profitability do. These findings highlight the need for improved tax oversight, as businesses with greater scale and profitability are more likely to engage in tax avoidance.